Factors influencing Ludwigs Angina (Bangladesh Journal of Otorhinolaryngology, 2015)
Introduction: Ludwigs angina is a rapidly progressive, potentially fulminant cellulitis involving the sub-lingual, submental and sub-mandibular spaces. It typically originates from an infected or recently extracted tooth, most commonly the lower second and third molars. Besides, poor nutritional status, lack of proper medical supports are still major predisposing factors in developing Ludwigs angina in countries like Bangladesh. Aim: Our study aimed to observe etiological factors, clinical presentations, causative agents and treatment response. Method: We carried out a cross sectional study among 26 patients with Ludwigs angina admitted in the department of ENT and Head-neck surgery in Mitford Hospital from January- December-2012. Results: In this study we found that males are predominantly affected than females (22 males and 4 females, ratio-5.5:1) with odontogenic infection (15, 57%) as source. We found history of recent tooth extraction in 5 cases (19.2%) & organism was isolated from pus culture, Klebsiella in 5 cases (19.2%) out of 13 cases. In this study we found tooth cleaning habit of patients by tooth brush18 cases (69.2%). We elicited underlying systemic disease mainly Diabetes Mellitus in 4 cases (15.3%) and Chronic renal failure in some of our cases but could not reach in a conclusion as to whether systemic illness predisposes to Ludwig angina. Conclusion: Our study suggests that prompt and thorough clinical evaluation and definitive care will considerably improve patient condition and reduce morbidity and mortality. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22010 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 5-7